The Multiple Generations in Adult and Higher Education Classrooms: What We Assume, What We Know, What We Can Learn, and What May Be Missing - Catherine Hansman; Kathryn McAtee (Adult Education Research Conference, 2009)
The purpose of this paper is to gain greater understandings of the “generation” literature as it relates to adult learners in higher and adult education contexts. We also analyze the literature from a critical perspective, considering how the literature attends to issues of gender, race, ethnicity, class, and sexual identity.